2018
DOI: 10.2174/1389557516666160928162724
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on the Biological and Pharmacological Activities of Rhodanine Based Compounds for Research and Development of Drugs

Abstract: At present, diseases resulting from various reasons have been causing deadly fears to humans and previously incogitable losses to health. Meanwhile, the patient compliance has been weakening because of drug resistance and serious drug adverse effects. There is therefore an urgent need for the development of novel structural agents. Rhodanine derivatives have exhibited wide biological activities, as well as significant industrial applications, which suggests that rhodanine heterocycle represents a key structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Although rhodanines are recognized as potential pharmacophores for clinically active drugs, they have also been identified as members of the class of “pan-assay interfering compounds” (i.e., “PAINS”), so we followed suggested best practices and rigorously confirmed the validity of these hits through several subsequent in vitro and in vivo experiments (described below). Compound II-1 was then selected for further investigation, and a dose–response curve for the ELISA yielded an IC 50 of 1 μM (Figure D) with a Hill slope of ∼1, as expected for a 1:1 binding interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Although rhodanines are recognized as potential pharmacophores for clinically active drugs, they have also been identified as members of the class of “pan-assay interfering compounds” (i.e., “PAINS”), so we followed suggested best practices and rigorously confirmed the validity of these hits through several subsequent in vitro and in vivo experiments (described below). Compound II-1 was then selected for further investigation, and a dose–response curve for the ELISA yielded an IC 50 of 1 μM (Figure D) with a Hill slope of ∼1, as expected for a 1:1 binding interaction.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, derivatives were synthesized by reacting 2- Rhodanine is a bioactive molecule having antiinflammatory, antibacterial, antifungal, antiviral, antidiabetic, anticancer and antitubercular activities 9 . A study by Havrylyuk et al, 10 reported the synthesis and anticancer activity of 4-thiazolidinones containing benzothiazole moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Positions 3 and 5 in the rhodanine ring were revealed to be chemically more reactive; this plays a significant role in the design and development of new drug-like molecules [21,22]. To present the information available in the scientific literature about molecules in this group in a more efficient way, we divided them according to the method of substitution into 3-substituted, 5-substituted, and 3,5-disubstituted rhodanine derivatives.…”
Section: Rhodanines With Anticancer Propertiesmentioning
confidence: 99%
“…Among the reviews that have described the biological activity of rhodanines in the last decade, the anticancer activity was described in subsections of the whole review papers [20][21][22][23]. There is only one review that strictly describes the anticancer activity of Among the reviews that have described the biological activity of rhodanines in the last decade, the anticancer activity was described in subsections of the whole review papers [20][21][22][23]. There is only one review that strictly describes the anticancer activity of rhodanines [24].…”
Section: Introductionmentioning
confidence: 99%